Single- and Multimarker Genome-Wide Scans Evidence Novel Genetic Risk Modifiers for Venous Thromboembolism - Herrera-Rivero, Marisol; Stoll, Monika; Hegenbarth, Jana-Charlotte; Rühle, Frank; Limperger, Verena; Junker, Ralf; Franke, André; Hoffmann, Per; Shneyder, Maria; Stach, Michael; Nowak-Göttl, Ulrike (Thrombosis and Haemostasis, 2021)
Previous genome-wide association studies (GWASs) have established several susceptibility genes for venous thromboembolism (VTE) and suggested many others. However, a large proportion of the genetic variance in VTE remains unexplained. Here, we report genome-wide single- and multimarker as well as gene-level associations with VTE in 964 cases and 899 healthy controls of European ancestry. We report 19 loci at the genome-wide level of association (p ≤ 5 × 10−8). Our results add to the strong support for the association of genetic variants in F5, NME7, ABO, and FGA with VTE, and identify several loci that have not been previously associated with VTE. Altogether, our novel findings suggest that 20 susceptibility genes for VTE were newly discovered by our study. These genes may impact the production and prothrombotic functions of platelets, endothelial cells, and white and red blood cells. Moreover, the majority of these genes have been previously associated with cardiovascular diseases and/or risk factors for VTE. Future studies are warranted to validate our findings and to investigate the shared genetic architecture with susceptibility factors for other cardiovascular diseases impacting VTE risk.
Keywords: genome wide association studies; venous thromboembolism; genetic risk; susceptibility loci